The influence of subject learning on the skills of decoding autofluorescent images of the oral mucosa - A. A. Rykhlevich; Ya. P. Sandakov; A. V. Kochubey; V. V. Kochubey (Acta Biomedica Scientifica, 2021)
Background. Despite the ease of implementation, harmlessness, painlessness and speed of the study, the method of autofluorescence does not belong to the routine and often used because of the dependence on the skill of the dentist in interpretation of the resulting visualization. Foreign and domestic researchers speak about the need for thematic training of dentists for the widespread introduction of the autofluorescence method into practice. There is no data proving the influence of training on the skill of interpretation autofluorescence images and showing the dependence of the skill on the duration of training and its frequency.The aim of the study was to conduct a comparative analysis of the results of interpreting autofluorescence images of the oral mucosa by dentists before and after thematic training.Methods. 308 dentists interpreted 20 images of autofluorescence of the oral mucosa before and after the thematic training, 10 of them were of potentially malignant diseases of the oral mucosa, 10 – of benign lesions and paraphysiological anomalies. Correctly identified mucosal changes presented in the autofluorescence image were considered positive results of decoding. The results were evaluated relative to the duration of training and its frequency, taking into account the duration of breaks, according to the average number of positive results.Results. Before the thematic training, dentists on average decoded 8.41 ± 4.89 images, after training – 12.11 ± 3.12 images. The difference before and after the thematic training between the number of positive results of interpretation autofluorescence images is statistically significant (t = –14.1, p˂ 0.001). There was no significant difference in the results of interpretation potentially malignant oral diseases (F = 1.67; p = 0.190) and benign lesions and conditions (F = 0.647; p = 0.524) between the three groups that studied for 6, 12 and 18 hours. There is a correlation to the duration of the interruption of training with positive results of decoding (r = –0.3376; p˂ 0.001). The positive results of interpretation of autofluorescence with regular monthly 6-hour training had significant increasing trends (12.11 ± 3.12 and 13.22 ± 1.76, t = –3.41, p = 0.001; 13.22 ± 1.76 and 14.40 ± 1.81, t = –4.74, p˂ 0.001).Conclusion. Thematic training improves the skill of interpretation autofluorescence images in dentists. The regularity of short-term training is more important for maintaining the interpretation skill than the duration of training.